Abcès parodontal palatin v/s carcinome : approche clinique - Hiam WEHBÉ; Edgard NEHMÉ; Jeanine HOYEK-GEBEILY (International Arab Journal of Dentistry (IAJD), 2011)
The periodontal abscess is a localized purulent infection that affects the tissues surrounding a periodontal pocket and causes the destruction of tooth supporting structures. Various etiologies have been proposed. The symptoms and the clinical aspect often guide the practitioner toward the diagnosis and treatment choices of this entity, particularly in its palatal location. This case report is interesting because of the uncommon associated signs and symptoms, the concomitance of other mucosal lesions, the management and therapeutic approach adopted and the followup of the patient during the healing phase.